Suplementação no período das águas de bovinos e bubalinos recriados em pastagem de capim-xaraés (Urochloa brizantha Syn. Brachiaria brizantha cv. Xaraés) - Silva, Daiane Cristina Marques da [UNESP] (2015)
The objective of this study was evaluate the supplementation method of 20 beef cattle [Nelore; 10 + 1 month of age and 220 + 33kg body weight (BW)] and 20 buffaloes [Murrah water buffalo, 10 + 1 month of age and 206 + 29kg body weight (BW)] growing in (Urochloa brizantha cv. Xaraés) receiving supplementation (0.6% BW), or not (control). Animals were divided in two treatment groups (n = 10 animals of each genetic group for each treatment). Body weight were conducted at the beginning of the experiment (0d) and 28, 56 and 84 day, to determining weight gain (WG), average daily gain (ADG), and blood samples for determination of glucose. Hip height measurements (HH), body condition score (BCS), rib eye area (REA), backfat thickness - 12th rib (BF), rump fat thickness (RFT) were determined at the beginning (0d) and the end (84d) of the study. The evaluation of feeding behavior was conducted (trough time, rumination, idleness and water intake) considering the time spent on each event. Cost of different treatments was calculated. There was no interaction between species and treatment.The beef cattle had higher values (P <0.01) of BW0d, BW28d, BW56d, BW84d, WGtotal, ADG28d, ADG56d, ADG84d, ADGtotal, HH0d, HH84d, REA84d (P = 0.04), total cost/head (P = 0.03) and income/head/ha when compared to buffaloes. Buffaloes had higher values (P < 0.01) of BCS0d, BCS84d, BF0d, BF84d, RFT0d, RFT84d, length of stay in the trough, water intake, and percentage supplement intake compared to beef cattle. Effect of treatment was detected (P < 0.01) for BW0d, BW28d, BW56d, BW84d, WGtotal, ADG28d, ADG56d, ADG84d, ADGtotal, BCS84d, REA84d, total cost/head, gain/@, income/head where supplemented animals showed higher values when compared to control animals. In conclusion, bovine genetic group excelled for weight gains while consuming a smaller proportion of ...